Blinkers in the solar transition region - Ashbourn, J; Woods, L; Kennedy, D (Springer Berlin Heidelberg, 2017)
In this paper it is shown that the small flare-like patches known as ‘blinkers’ may be explained as the result of an instability in transition layer magnetic flux tubes, which are represented by a set of isolated, high-aspect ratio vertical cylinders as the legs of coronal plasma loops. An essential prerequisite for the instability is that the heating, which is assumed to be only due to ohmic dissipation, closely balances the radiation losses. The instability occurs in the plasma pressure and could be triggered by a random shock wave; it rapidly increases the local pressure and results in a minor ‘explosion’. By dissipating energy away from the region, this reduces the local pressure and restores stability on a timescale of a few minutes, which is in agreement with observations of blinkers. The theory is an extension of Ashbourn and Woods’ previous treatment of the transition layer differential emission measure.